Research progress of rare earth separation methods and technologies - Traore, Mory; Gong, Aijun; Wang, Yiwen; Qiu, Lina; Bai, Yuzhen; Zhao, Weiyu; Liu, Yang; Chen, Yi; Liu, Ying; Wu, Huilin; Li, Shuli; You, Yueyi (Journal of rare earths, 2023)
Strategical elements, such as rare earth elements, play a crucial role in the industry, especially in producing high-tech materials. Major global industries have developed a strong dependence on rare earth materials. Every year, there are innovations in industries such as modern technology, green energy, or communications technology, which need more strategic metals to improve investment profitability. This article reviews advances in rare earth separation methods and techniques to guide and recommend the best extractants, depending on leaching conditions and the final target product. Each method for separating and extracting agents is individually revised in terms of the mechanism and interaction of providing rare earth elements. This paper also evaluates past and current trends of these methods and technical extractants and identifies their strengths and weaknesses. This review summarized the research progress of methods applied by industries to extract rare earth elements used in up-to-date advanced technology. The research shows a broad and deep understanding of REE and provides further information on the scientific aspect. Four significant methods of REE are distinguished and were profoundly described. These include liquid–liquid separation, solid–liquid extraction, column chromatographic separation, and solid extraction and separation methods. [Display omitted]